KREDIBILITAS MEDIA ONLINE DALAM PANDANGAN MAHASISWA - Loisari Hoerunnisa; Khoiruddin Muchtar; Cecep Suryana (LPPM Abdurrab Pekanbaru, 2020)
Abstract: The purpose of this research is to find out how Journalism Communication Science students perceive the credibility of Detik.com Online Media, which includes three dimensions, namely trustworthiness, current, and unbiased. The method used in this study is a qualitative descriptive method, using in-depth interviews and field observations. The methodology with a qualitative approach is used in order to have a complete and in-depth picture of the problem under study. The results of this study concluded that the credibility of Detik.com Online Media in the view of Communication Studies Journalism students at UIN Sunan Gunung Djati Bandung was positive. Broadly speaking, Detik.com Online Media is credible media. However, there are a number of things that need to be reviewed in the news presentation system which are presented gradually under different titles but are still in one issue, but that does not affect students' opinions about the belief in reporting on Detik.com Online Media.